Attribution Bias in Major Decisions: Evidence from the United States Military Academy - Kareem Haggag; Richard W. Patterson; Nolan G. Pope; Aaron Feudo (Center for Economic Studies and ifo Institute (CESifo), 2018)
Using administrative data, we study the role of attribution bias in a high-stakes, consequential decision: the choice of a college major. Specifically, we examine the influence of fatigue experienced during exposure to a general education course on whether students choose the major corresponding to that course. To do so, we exploit the conditional random assignment of student course schedules at the United States Military Academy. We find that students who are assigned to an early morning (7:30 AM) section of a general education course are roughly 10% less likely to major in that subject, relative to students assigned to a later time slot for the course. We find similar effects for fatigue generated by having one or more back-to-back courses immediately prior to a general education course that starts later in the day. Finally, we demonstrate that the pattern of results is consistent with attribution bias and difficult to reconcile with competing explanations.
Keywords: D91; I23; 330; attribution bias; college major